2012
DOI: 10.1248/bpb.35.601
|View full text |Cite
|
Sign up to set email alerts
|

Exon 10 Coding Sequence Is Important for Endoplasmic Reticulum Retention of Endoplasmic Reticulum Aminopeptidase 1

Abstract: Endoplasmic reticulum aminopeptidase 1 (ERAP1) is a final trimming enzyme of N-extended antigenic peptides bound to major histocompatibility complex class I molecules in the endoplasmic reticulum (ER). In our previous work, we found that ERAP1 is secreted from macrophages in response to activation by lipopolysaccharide and interferon-γ. In this paper, we searched for the amino acid sequence of ERAP1 protein important for ER retention by constructing chimeric proteins and found that the sequence between 485 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…In our previous work, we reported that the exon 10 coding sequence of ERAP1 was critical for its ER retention (38). Certain proteins binding to the exon 10 sequence might be required for the ER retention of ERAP1.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous work, we reported that the exon 10 coding sequence of ERAP1 was critical for its ER retention (38). Certain proteins binding to the exon 10 sequence might be required for the ER retention of ERAP1.…”
Section: Discussionmentioning
confidence: 95%
“…As a result, it has been hypothesized that they are retained through the interaction with other ER resident proteins (4). In ERAP1, a 23-amino acid sequence encoded by exon10 of the gene and predicted to be unstructured was initially implicated in that function (45). Recently, Erp44, an ER resident protein disulfide isomerase, has been shown to retain ERAP1 inside the ER through the formation of a mixed disulfide bond with a cysteine residue in the exon 10 loop (46).…”
Section: The Exon 10 Loop Is Structured and Contains A Disulfidementioning
confidence: 99%
“…GXMEN and HEXXH motifs have been reported to be encoded by exon 6 while 19 amino acids downstream from the HEXXH motif encoded by exon 7 is the glutamic acid residue, which together with the two histidine residues in HEXXH motif binds the zinc ion. 12) Phylogenetic analysis of M1-aminopeptidase family also implies a divergence in ERAP from P-LAP/IRAP 2) ( Fig. 1).…”
Section: Two Forms Of Erap1mentioning
confidence: 93%
“…2). While we identified and initially designated these two isoforms as A-LAPa and A-LAPb, 12) another group termed them as ERAP1b and ERAP1a, respectively. 14) To avoid nomenclature confusion, the isoforms encoded by these mRNAs were re-designated as ERAP1-19E and ERAP1-20E, respectively.…”
Section: Two Forms Of Erap1mentioning
confidence: 99%